2015
DOI: 10.1371/journal.pone.0123367
|View full text |Cite
|
Sign up to set email alerts
|

Association of Small Dense LDL Serum Levels and Circulating Monocyte Subsets in Stable Coronary Artery Disease

Abstract: ObjectiveAtherosclerosis is considered to be an inflammatory disease in which monocytes and monocyte-derived macrophages play a key role. Circulating monocytes can be divided into three distinct subtypes, namely in classical monocytes (CM; CD14++CD16-), intermediate monocytes (IM; CD14++CD16+) and non-classical monocytes (NCM; CD14+CD16++). Low density lipoprotein particles are heterogeneous in size and density, with small, dense LDL (sdLDL) crucially implicated in atherogenesis. The aim of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 49 publications
(59 reference statements)
4
30
0
2
Order By: Relevance
“…Several studies indicated a direct role of sdLDL in atherogenesis and provided solid evidence that the role of sdLDL goes beyond a simple marker of metabolic disorder. These particles exhibit reduced binding capacities to LDL-receptors and show a stronger affinity to the extracellular matrix within the vascular wall [37,38]. Consistent with these findings, a significant difference in LDL-C levels was also observed between subjects with subclinical atherosclerosis and those without in the present study, however, the lack of sdLDL determination is a limitation of the study.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies indicated a direct role of sdLDL in atherogenesis and provided solid evidence that the role of sdLDL goes beyond a simple marker of metabolic disorder. These particles exhibit reduced binding capacities to LDL-receptors and show a stronger affinity to the extracellular matrix within the vascular wall [37,38]. Consistent with these findings, a significant difference in LDL-C levels was also observed between subjects with subclinical atherosclerosis and those without in the present study, however, the lack of sdLDL determination is a limitation of the study.…”
Section: Discussionsupporting
confidence: 88%
“…+ monocytes have a pro-inflammatory profile in blood as activated-macrophages in connective tissue, and their proportion is expanded in various infectious and inflammatory diseases [6,9,21] . We observed not only a higher proportion of CD14 ++ /CD16 + in patients with pre-dialysis CKD and HD patients compared to controls, but also that this differentiation may be induced by exposure to uremic sera, and sera from advanced CKD stages promoted a more substantial shift toward the CD14 ++ /CD16 + profile.…”
Section: Discussionmentioning
confidence: 99%
“…+ is substantially increased in inflammatory conditions [6,8,9] , including CKD [8] and has been linked to cardiovascular complications in hemodialysis (HD) and non-dialysis CKD patients [10,11] . However, processes underlying the functional shift toward blood CD14 ++ /CD16 + monocytes in CKD remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is not unexpected that the ApoB/ApoA-I ratio was closely related with TG, TC, HDL-C and LDL-C. Apolipoprotein B and A-I are the major protein moieties of LDL and HDL, respectively. The level of ApoB reflects the number of potentially atherogenic particles 17. Meanwhile, ApoA-I plays an important role in removing excess cholesterol from tissues and incorporating it into HDL for reverse transport to the liver, forming the basis for atheroprotective events 18…”
Section: Discussionmentioning
confidence: 99%